KRAS‐Mutated, Estrogen Receptor‐Positive Low‐Grade Serous Ovarian Cancer: Unraveling an Exceptional Response Mystery. (2nd March 2021) - Kato, Shumei; McFall, Thomas; Takahashi, Kenta; Bamel, Kasey; Ikeda, Sadakatsu; Eskander, Ramez N.; Plaxe, Steven; Parker, Barbara; Stites, Edward; Kurzrock, Razelle
Abstract: : We report on a woman with aggressive estrogen receptor‐positive, KRAS ‐mutated ovarian cancer who achieved a remarkable response to combination therapy with the MEK inhibitor (trametinib) and the aromatase inhibitor (letrozole), even though the disease had failed to respond to a combination of a PI3K inhibitor and different MEK inhibitor, as well as to trametinib and the estrogen modulator, tamoxifen, and to letrozole by itself. The mechanism of action for exceptional response was elucidated by in vitro experiments that demonstrated that the fact that tamoxifen can have an agonistic effect in addition to antagonist activity, whereas letrozole results only in estrogen depletion was crucial to the response achieved when letrozole was combined with an MEK inhibitor. Our current observations indicate that subtle variations in mechanisms of action of outwardly similar regimens may have a major impact on outcome and that such translational knowledge is critical for optimizing a precision medicine strategy. Key Points: This report describes the remarkable response of a patient with KRAS ‐mutated, estrogen receptor‐positive low‐grade serous ovarian cancer treated with trametinib (MEK inhibitor) and letrozole (aromatase inhibitor), despite prior progression on similar agents including tamoxifen (estrogen modulator). In vitro investigation revealed that tamoxifen can have agonistic in addition to antagonistic effects, which could be the reason for the patient not responding to the combination of trametinib and tamoxifen. The current observations suggest that drugs with different mechanisms of action targeting the same receptor may have markedly different anticancer activity when used in combinations. Abstract : This article reports the case of a patient with aggressive estrogen receptor‐positive, KRAS ‐mutated ovarian cancer who achieved a remarkable response to combination therapy with the MEK inhibitor trametinib and the aromatase inhibitor letrozole, despite earlier failures of treatment with other combination inhibitor treatment. This article focuses on the possibility that subtle variations in mechanisms of action of outwardly similar regimens may have major effects on patient outcomes.